2019
DOI: 10.1074/jbc.ra119.007535
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distinct rate-limiting steps in the cleavage of alkenes by carotenoid cleavage dioxygenases

Abstract: Edited by F. Peter Guengerich Carotenoid cleavage dioxygenases (CCDs) use a nonheme Fe(II) cofactor to split alkene bonds of carotenoid and stilbenoid substrates. The iron centers of CCDs are typically five-coordinate in their resting states, with solvent occupying an exchangeable site. The involvement of this iron-bound solvent in CCD catalysis has not been experimentally addressed, but computational studies suggest two possible roles. 1) Solvent dissociation provides a coordination site for O 2 , or 2) solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In the subsequent 3-L bioreactor fermentation, it was found that the DO was a very important factor for the biosynthesis of β-ionone. This is consistent with a recent report [47] and is related to the last metabolic step of β-ionone biosynthesis, which is catalyzed by carotenoid cleavage dioxygenase and requires two oxygen molecules to produce two β-ionone molecules. Thus, with the optimization of DO level at 15% the yield of β-ionone increased twofold compared to the bioreactor fermentation performed with DO at 0-5%.…”
Section: Discussionsupporting
confidence: 93%
“…In the subsequent 3-L bioreactor fermentation, it was found that the DO was a very important factor for the biosynthesis of β-ionone. This is consistent with a recent report [47] and is related to the last metabolic step of β-ionone biosynthesis, which is catalyzed by carotenoid cleavage dioxygenase and requires two oxygen molecules to produce two β-ionone molecules. Thus, with the optimization of DO level at 15% the yield of β-ionone increased twofold compared to the bioreactor fermentation performed with DO at 0-5%.…”
Section: Discussionsupporting
confidence: 93%
“…The normal sKIE observed for CAO1 was suggestive of proton transfer during the rate-limiting step of the reaction, although the exact proton source could not be pinpointed. Interestingly, inverse sKIE behavior could be conferred to CAO1 by substitution of a single amino acid residue (Leu509) located near the iron-solvent compex to Val as is found in NOV2 [76].…”
Section: Mechanistic Studiesmentioning
confidence: 83%
“…This issue was later revisited using purified protein and optimized reaction conditions with results clearly supporting dioxygenase chemistry [43]. More recently, solvent kinetic isotope effect (sKIE) studies have been carried out on NOV2 and CAO1 to determine the impact of deuterium substitution on steady-state kinetics [76]. These studies revealed a striking difference in behavior with NOV2 and CAO1 exhibiting inverse and normal sKIEs on k cat , respectively.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…The cleavage of a β-carotene by CCD1 requires two oxygen molecules to produce two β-ionone molecules. The presence of considerable amounts of β-carotene seen in our experiments suggests that despite oxygen supply in flasks during fermentation may be insufficient, limiting the activity of PhCCD1 ( Khadka et al, 2019 ; Liu et al, 2021 ). This explanation raises the possibility that both the YLBI3120 and YLBI3121 strains have the potential to produce even higher concentrations of β-ionone under optimal fermentation conditions.…”
Section: Discussionmentioning
confidence: 72%